Burning characteristics of single particles of coal and wood mixtures for co-firing in an upward-flowing hot gas stream - Mock, Chinsung; Lee, Hookyung; Choi, Sangmin; Yang, Won; Manovic, Vasilije (Elsevier, 2017)
This study presents the comparative burning behaviours of single solid particles of coal and biomass mixtures for co-firing. In this experimental investigation, a direct observation approach was used to investigate the ignition, flame characteristics and combustion times by means of high-speed photography at 7000 frames per second. Single particles were entrained into a hot gas stream at 1340 K and a rapid heating rate of 104–105 K/s. The apparent volatile flames from the prepared particle size groups were observed within 20–50 ms. To assess the effect of oxygen concentration, particles were burned for their flame characteristics in a range of 10%–40% O2. The test particles were sieved into three size groups (215–255 μm, 255–300 μm and 300–350 μm) to assess the effect of particle size. Special particles for the co-firing effect were collected individually from two types of mixed pellet: 20:80 and 50:50 coal/wood. Pure sub-bituminous coal and wood particles were also prepared in order to compare their combustion behaviours. In the experimental setup with a cross-injection configuration, sequential combustion processes were effectively and clearly described in terms of particle displacement with time. The experimental results showed distinguishable flame characteristics from single particles of coal, 50:50 coal/wood, 20:80 coal/wood and wood, including soot flame size and intensity. The impact of high coal-blending ratio caused an increase in the flame size and intensity and the ignition time was close to that of pure coal particles. Quantitative measurements of combustion events on co-firing particles were also discussed in relation to significant impacts of the particle size and the oxygen concentration.